JEJAK AUSTRONESIA DI SITUS GUA GEDE, PULAU NUSA PENIDA, BALI - Ati Rati Hidayah (Balai Arkeologi Bali, 2017)
The spread of Austronesian-speaking people to Southeast Asia and the Pacific Island happened about 3.500- 4.000 years ago through some routes. Nusa Penida Island located at a strategic place, at the edge of western route to eastern route or vice versa. So that, it is interesting to be studied. This research aims to trace the trail of Austronesian speakers occupancy in Gua Gede Site. The research method uses pottery residue analysis and context of the overall findings quantity. The finding of pottery at Gua Gede Site indicates the existence of Austronesian speakers at the site. Gua Gede was occupied by Austronesia speakers around 3.051±25 BP. Based on the result of the pottery residue analysis, plant utilization had been done and there was indication of subsistence alteration from hunting and food gathering to simple farming. Penyebaran penutur Austronesia ke wilayah Kepulauan Asia Tenggara dan Kepulauan Pasifik berkisar antara 3.500-4.000 tahun yang lalu melalui beberapa jalur. Pulau Nusa Penida terletak di wilayah yang strategis di ujung perbatasan jalur barat menuju ke timur atau sebaliknya, sehingga menarik untuk diteliti. Penelitian ini bertujuan untuk melihat adanya jejak penghunian Situs Gua Gede oleh Penutur Austronesia. Metode penelitian menggunakan analisis residu gerabah dan konteks kuantitas temuan secara keseluruhan. Temuan gerabah di Situs Gua Gede mengindikasikan adanya penghunian penutur Austronesia di situs tersebut. Gua Gede dihuni oleh penutur Austronesia pada 3.051±25BP. Berdasarkan dari hasil analisis residu gerabah, telah dilakukan pemanfaatan tumbuhan dan terdapat indikasi perubahan subsistensi dari berburu dan mengumpulkan makanan menjadi bercocoktanam sederhana.